PENGGUNAAN MEDIA TAMINORE HUNT BERPENGARUH TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG DISMENORE - Ayu, Dea; Ningsih, Lisma; Ismiati, Ismiati (Poltekkes Kemenkes Bengkulu, 2023)
One of the characteristics of puberty in adolescent girls is the occurrence of menstruation. When menstruation is usually often accompanied by dysmenorrhea. Dysmenorrhea can interfere with adolescent activity, cause cysts and other gynecological problems. Dysmenorrhea occurs after 2-3 years after menarche. In, Indonesia the dysmenorrhea rate is 64.25%. This study aims to determine the effect from the use of the taminore hunt media on the knowledge of young women about dysmenorrhea in SMP Negeri 5 Bengkulu City. This type of research is a pre-experimental one group pretest and posttest design. The sample in this study were students of grade VII and VIII of SMP Negeri 5 Bengkulu City, totaling 32 people. Sampling using a purposive sampling technique. Data analysis in this study used the test, Wilcoxon. The results of the study of the average knowledge before being given taminore hunt media amounted to 5.1562 and after being given media taminore hunt amounted to 13.6562. Based on the test Wilcoxon the value of p- value = 0.000 <0.05 shows that there is an influence after being given the media taminore hunt on the knowledge of young women about dysmenorrhea in SMP Negeri 5 Bengkulu City. Suggestions for this research, it is hoped that the Taminore Hunt media can become a learning medium to provide information about health and this media can be developed again